ANALISIS PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS VII DI SEKOLAH MTS NEGERI 01 PAMULANG TANGERANG SELATAN: PENDEKATAN METODE LITERATURE STUDY AND REVIEW (LSR) - Rozak, Abdul (STAI Bani Saleh, 2023)
This study uses the Literature Study and Review (LSR) method, which collects information related to the research topic from various literary sources. The results of the analysis show that Islamic religious education teachers have a very important role in shaping the religious character of class VII students at MTS Negeri 01 Pamulang. Teachers are responsible for providing appropriate religious lessons, guiding students in worship and improving attitudes and behavior in accordance with Islamic teachings. Through interactive, inspirational and contextual learning, teachers can inspire students to develop a deep understanding of religious values, practice Islamic teachings in everyday life, and form strong religious personalities. Teachers should set good examples and role models for students in practicing religious values ​​in everyday life. In addition, cooperation between teachers, parents and schools is needed to create an environment that supports the formation of students' religious character. Future research may include collecting primary data such as observation, interviews or questionnaires to gain a deeper understanding of the role of Islamic religious teachers in shaping students' religious character.